Development as conscientization : the case of Nijera Kori in Bangladesh - Barkat, Abul.; Human Development Research Centre (Dhaka, Bangladesh) (Dhaka : Pathak Shamabesh, 2008)
Socioeconomic impact of the work by Nijera Kori, non-government organization, on the poor people in rural Bangladesh.
"HDRC."
Includes bibliographical references (p. [445]-449) and index.
Keywords: Nijera Kori (Organization); Non-governmental organizations -- Bangladesh; Rural poor -- Bangladesh